Trauma and the perinatal period: A review of the theory and practice of trauma‐sensitive interactions for nurses and midwives - Sophie Isobel (Nursing Open, 2023)
Abstract Aim With high rates of trauma in the population, known links between trauma and perinatal distress, and the intimate and close nature of the nursing and midwifery roles, ensuring awareness and understandings of trauma is crucial for guiding practice. This paper aims to explore the relationship of trauma to the perinatal period, based on theory and practice, to consider on how nurses and midwives can deliver trauma‐sensitive interactions. Design and Methods This discursive discussion draws on relevant research from the fields of trauma therapy, attachment theory and nursing and midwifery practice to consider elements of trauma‐sensitive practice in the perinatal period. Results Nurses and midwives can foster safety for people who have experienced trauma through noticing and responding to triggers, supporting awareness of attachment and its relationships to trauma, undertaking psychosocial screening with care, supporting linearity and cohesion in narratives and developing collaborative care plans that maximise safety and agency. For nurses and midwives, understandings of the relationship between trauma, pregnancy, birth, early parenting and distress is crucial for effective care delivery. Delivering perinatal nursing or midwifery care of any kind, without universal trauma precautions risks reinforcing, misinterpreting or re‐enacting dynamics of trauma. To be trauma‐sensitive in this period requires nurses and midwives to have awareness of the dynamics of trauma in relation to pregnancy, birth and attachment. Implications for the Profession and/or Patient Care This paper fills a gap in the translation of theory to practice for trauma‐sensitive care in the perinatal period, with a focus on the therapeutic relationship formed by nurses and midwives. The findings highlight that nurses and midwives can foster safety for people who have experienced trauma within their practice, when they hold a robust understanding of the relationship between trauma, pregnancy, birth, early parenting and distress. Patient or Public Contribution No patient or public contribution.